Morfometri Kepiting Air Tawar Parathelphulsa maindroni Dari Dua Tipe Habitat di Taman Nasional Gunung Palung Kalimantan Barat - Junardi Junardi; Ina Idola; Tri Rima Setyawati (UNIVERSITAS NEGERI PADANG, 2020)
Freshwater crab Parathelphusa maindroni can live in various types of aquatic habitats. High adaptability can cause differences in body size in response to diverse habitat conditions. This species has been found at Stasiun Cabang Panti Gunung Palung National Park, West Kalimantan, in two different habitat types ununfortunately data on body size is still not available. The purpose of this study was to distinguish the morphometric characteristics of P. maindroni from two different habitats. The P. maindroni crabs were collected with traps and searched using a dip net. Morphometric analysis using 12 characters of body parts. The number of specimens was collected as many as 52 individuals, 28 individuals from river and 24 individuals from freshwater swamp habitat. The freshwater crab P. maindroni that lives in two different types of habitat can only be identified based on the width of the carapace, this character can also be used to differentiate of sex.